Uji Validitas dan Reliabilitas Benign Prostatic Hyperplasia Impact Index Versi Bahasa Indonesia - Jessica Firajanti A. Kumpang; Eka Yudha Rahman; Oski Illiandri (Homeostasis, 2020)
Abstract: Benign Prostatic Hyperplasia (BPH) is a chronic disease that affects quality of life. The assessment can be performed using a specific quality of life questionnaire for BPH patients, one of the questionnaires is the Benign Prostatic Hyperplasia Impact Index (BII). However, BII cannot be used in Indonesia because it has not been translated and tested for validity and reliability. The purpose of this study is to translate BII into Indonesian and assess the validity, and reliability of the Indonesian version of BII. This study is descriptive with a cross-sectional approach. The translation is carried out according to standardized guidelines. A minimum number of samples was determined by respondent-item ratio of 5:1 and was adjusted to the inclusion and exclusion criteria. The content validity was assessed by experts, construction validity was analyzed by the Pearson correlation test, and internal construction reliability was adjusted with Cronbach's alpha values. A total of 23 BPH patients were obtained as sample with a mean age of 67.13±10.61. The Indonesian version of the BII questionnaire was declared valid related to content validity and construction validity (r count=0.853-0.938, r table 0.4132, p <0.05), and was highly reliable (α= 0.908). Keywords: benign prostatic hyperplasia (BPH), benign prostatic hyperplasia impact index (BII), validity, reliability. Abstrak: Benign Prostatic Hyperplasia (BPH) merupakan penyakit kronis yang dapat mengganggu kualitas hidup. Penilaian kualitas hidup dilakukan menggunakan kuesioner penilaian kualitas hidup khusus BPH, salah satunya Benign Prostatic Hyperplasia Impact Index (BII). Namun, BII belum bisa digunakan di Indonesia karena belum diterjemahkan, belum diuji validitas, dan reliabilitasnya. Tujuan penelitian ini adalah menerjemahkan BII ke dalam Bahasa Indonesia, menilai validitas, dan reliabilitasnya. Penelitian ini merupakan penelitian deskriptif dengan pendekatan potong lintang. Penerjemahan mengikuti pedoman terstandardisasi. Besar sampel minimal sesuai respondent-item ratio 5:1 dengan memperhatikan kriteria inklusi dan eksklusi.Validitas isi dinilai oleh ahli, validitas konstruksi dianalisis dengan uji korelasi Pearson, dan reliabilitas konstruksi internal dengan memperhatikan nilai Cronbach’s alpha. Total sampel 23 pasien BPH dengan rerata usia 67,13±10,61. BII versi Bahasa Indonesia valid terkait validitas isi dan konstruksi (r hitung=0,853-0,938, r tabel=0,4132, p=0,05), dan reliabilitasnya sangat tinggi (α=0,908). Kata-kata kunci: benign prostatic hyperplasia (BPH), benign prostatic hyperplasia impact index (BII), validitas, reliabilitas.